Difficulties in Evaluating Lyapunov Exponents for Lie Governed Dynamics - Sarris, C. M. (2013)
We consider here an environment in which the fact that a semiquantum Hamiltonian obeys SU(2) symmetries poses serious difficulties if one wants to compute Lyapunov exponents.